2008
DOI: 10.1016/j.tcb.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Phagosome maturation during the removal of apoptotic cells: receptors lead the way

Abstract: In metazoan organisms, cells undergoing apoptosis are rapidly engulfed and degraded by phagocytes. Defects in apoptotic-cell clearance result in inflammatory and auto-immune responses. However, little is known about how apoptotic-cell degradation is initiated and regulated and how different phagocytic targets induce different immune responses from their phagocytes. Recent studies in mammalian systems and invertebrate model organisms have led to major progress in identifying new factors involved in the maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 97 publications
(225 reference statements)
4
62
0
Order By: Relevance
“…that are recruited to phagosomes at different stages during their maturation Zhou and Yu, 2008). We found that TBC-2 was transiently recruited to phagosomes at a similar stage to RAB-5, which was followed by the recruitment of RAB-7 (Fig.…”
Section: Research Articlementioning
confidence: 64%
See 2 more Smart Citations
“…that are recruited to phagosomes at different stages during their maturation Zhou and Yu, 2008). We found that TBC-2 was transiently recruited to phagosomes at a similar stage to RAB-5, which was followed by the recruitment of RAB-7 (Fig.…”
Section: Research Articlementioning
confidence: 64%
“…The resulting intracellular vesicles containing ingested apoptotic cells, termed phagosomes, undergo a series of maturation steps leading to the destruction of cell corpses. Although the specific factors and mechanisms controlling maturation of apoptotic-cell-containing phagosomes are not well understood, recent studies in C. elegans indicate that cell corpse clearance through phagosome maturation follows a general path that requires similar components and cellular events to that of phagosomes carrying opsonized particles or microorganisms Vieira et al, 2002;Zhou and Yu, 2008). For example, Rab GTPases, the key regulators of endocytic transport and maturation of phagosomes with ingested opsonized cells or microbes, are also found to play important roles in the maturation of phagosomes containing apoptotic cells in both mammals and C. elegans Kitano et al, 2008;Lu et al, 2008;Mangahas et al, 2008;Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of ingested cellular material involves phagosome maturation through homotypic and heterotypic fusion of early endosomes, late endosomes and lysosomes (Zhou and Yu, 2008). The classical markers employed for the discrimination of these different phases are Ras-related protein 5 (Rab5), a small GTPase associated with early phagosomes (Kinchen et al, 2008;Desjardins et al, 1994), and annexin I (Anx1) or lysosomal-associated membrane protein 1 (LAMP1), two proteins that are utilized to show later phagosomal stages and phagosomes after lysosomal fusion, respectively (May and Machesky, 2001;Alvarez-Dominguez et al, 1997;Tjelle et al, 2000).…”
Section: Internalized Tumor Cell Fragments Colocalize With Phagosome mentioning
confidence: 99%
“…S2). Moreover, Rab5 GTPase, which has recently been shown to be crucial in macrophages in the final maturation process before degradation by the lysosomal enzymes occurs (Zhou and Yu, 2008), is expressed at normal levels in the Nuc1 RPE (supplementary material Fig. S2).…”
Section: Discussionmentioning
confidence: 99%